Revolutionizing marketing strategies: analyzing guerrilla marketing, brand image, and brand awareness impact on Gen Y purchasing decisions - Bilal Khalid (My University, 2024)
Abstract The rise of digital technology and social media platforms has made traditional marketing approaches less effective in capturing the attention of the tech-savvy Generation Y. There has been an increased interest in guerrilla marketing tactics, which employ unconventional strategies to engage consumers. This study investigated the impact of guerrilla marketing, brand image, and brand awareness on the purchasing decisions of Generation Y consumers. The study adopted the Hierarchy-of-Effects Theory and conducted an empirical study the following constructs: viral marketing, ambush marketing, buzz marketing, street graphics marketing, brand awareness, brand image, and purchase decision. Data was collected from 442 Generation Y respondents in Thailand. Confirmatory factor analysis was used to analyse the model and construct's reliability. At the same time, the partial least squares structural equation modelling technique was adopted to explore the relationship of the study constructs. The results indicated that the purchase decision of Generation Y was significantly influenced by ambush marketing, buzz marketing, and street graphics marketing. The research revealed that brand image and brand awareness exerted a substantial impact on purchase decisions and served as key mediators in the relationship between guerrilla marketing and purchase decisions among Generation Y. The study emphasised the importance of guerrilla marketing techniques and leverage of the power of social media to influence purchase behaviour. Marketing managers should consider these techniques to attract Generation Y.
Keywords: Brand Image; Brand extension; Marketing mix modeling; Consumer Behavior in Brand Consumption and Identification